(untitled) (Nordic Journal of African Studies, 2000)
This article looks at the teaching of the Bambara language in comparison with that of French in schools that practice convergent pedagogy. It is based on three field trips to Ségou in 1998-99, with classroom observation in the six grades of four primary schools. It states that whereas French is taught in a systematic way, with weight on grammar, Bambara is taught indirectly, through different exercises like memorisation of words, reading and writing according to the global method, and dictation. Rules to explain mistakes are hardly ever given, and the teachers themselves make mistakes, especially in word segmentation. The conclusion is that though the active pedagogical method seems to work well, the mother tongue instruction lags behind that of the second language, thus jeopardising the mother tongue proficiency that is supposed to ease the acquisition of the second language.